Electrochemical Behavior and Direct Quantitative Determination of Paclitaxel - Lang, Jiaqi; Wang, Wenting; Zhou, You; Guo, Dongqin; Shi, Rujie; Zhou, Nong (Frontiers in Chemistry, 2022)
The electrochemical behavior and direct quantitative determination of the Paclitaxel, a poorly soluble drug made into microemulsion, was researched by cyclic voltammetry in acetate buffer solutions (pH = 4.0) at glassy carbon electrode. The results show that the oxidation process is irreversible and controlled by diffusion. Moreover, the effects of anodic peak current (Ipa), anodic peak potential, scan rate, pH, and the electrochemical redox mechanism have been studied. The anodic peak current varied linearly with paclitaxel concentration in the range of 5×10-5 mol/L to 5×10-4 mol/L and detection limit was 9.15×10-8 mol/L. The results of RSD (0.90%) and recovery (99.22~101.69%) were obtained. Additionally, it is proved that one electrons and one protons involved in the process of the electrochemical redox. The present research has been successfully used to determine paclitaxel in pure and real samples, which further supported the electrochemical behavior investigation of Paclitaxel and direct determination of micro-emulsion.